Mooren''s ulcer. (August 2011) - Zelefsky, Joseph R; Srinivasan, Muthiah; Cunningham, Emmett T
Mooren''s ulcer (MU) is an inflammatory peripheral ulcerative keratopathy that occurs most commonly in the developing world. Recent evidence supports the notion that autoimmune mechanisms are involved in the pathogenesis of this disease. Patients with MU typically develop painful, progressive peripheral ulceration of the cornea that, if untreated, can lead to corneal perforation and blindness. Risk factors for the development of MU include HLA-DR17 haplotype expression, prior corneal surgery or trauma, and hookworm infestation. A thorough ocular and systemic history and clinical examination, together with directed laboratory testing, should be carried out to rule out other causes of corneal ulceration, including both infectious keratitis and peripheral ulcerative keratitis secondary to an underlying systemic autoimmune disease. Treatment of MU is often challenging, but typically includes local and/or systemic corticosteroids. Noncorticosteroid immunosuppressive agents, conjunctival resection or advancement and tectonic surgical repair have also been used with success in patients refractory to corticosteroid therapy.